Deep Eutectic Solvent‐Induced In Situ Etching and Phosphorization to Form Nickel Phosphides for Electrooxidation of 5‐Hydroxymethylfurfural. Issue 20 (15th September 2022) - Xu, Danxia; Yang, Yuechao; Zhang, Baolong; Yang, Zhaohui; Liu, Shuzi; Mu, Tiancheng
Abstract: The development of catalysts with relatively high current densities at low potentials for the electrooxidation of 5‐hydroxymethylfurfural (HMF) is still challenging. In this study, an in situ deep eutectic solvent (DES) etching phosphorization strategy is developed to prepare nickel phosphides encapsulated in P, O‐codoped carbon nanosheets (Ni−P@POC). The DES serves not only as an etchant to extract Ni 2+ from the nickel foam, but also as a phosphorus source to form nickel phosphides in situ uniformly embedded in the carbon films to produce a sheet structure. The electrooxidation performance is further greatly improved by implementing an electrochemical activation step to transform Ni−P@POC into NiOOH/Ni−P@POC (t‐Ni−P@POC). t‐Ni−P@POC exhibits a low onset potential of 1.20 V vs. RHE and a high current density of 200 mA cm −2 at 1.33 V vs. RHE for HMF electrooxidation, outperforming most reported catalysts. The as‐developed DES etching phosphorization strategy offers a facile, flexible, and universal route for the design of high‐performance catalysts with specific nanostructures. Abstract : Etch it better : A deep eutectic solvent‐induced in situ etching phosphorization strategy was proposed to prepare a nickel phosphide‐P, O‐codoped carbon nanosheet composite (t‐Ni−P@POC), which exhibits a low onset potential of 1.20 V vs. RHE and a high current density of 200 mA cm −2 at 1.33 V vs. RHE for electrooxidation of 5‐hydroxymethylfurural after electrochemical activation.